THU0081 MIR-17-5P REDUCES INFLAMMATION AND BONE EROSIONS IN COLLAGEN INDUCED ARTHRITIS MICE AND DIRECTLY TARGETS THE JAK-STAT PATHWAY IN RHEUMATOID ARTHRITIS FIBROBLAST-LIKE SYNOVIOCYTES. (2nd June 2020) - Najm, A.; Masson, F. M.; Preuss, P.; Georges, S.; Ory, B.; Quillard, T.; Veale, D.; Fearon, U.; Le Goff, B.; Blanchard, F.
Abstract : Background: micro-RNAs (miR) are strong regulators of gene expression. Their involvement in RA key cytokines pathway regulation entitles them as important players in RA pathophysiology. The miR 17-92 cluster has been widely studied in cancer as they regulate cell apoptosis. Objectives: The aims of this study were to screen miR 17-92 cluster's expression in different RA phenotypes (erosive and non erosive), further elucidate the mechanisms and direct targets involved in miR-17-5p anti-inflammatory role and to investigate miR-17-5p therapeutic effect in arthritis. Methods: A miR array was performed in synovial tissue from naïve erosive and non-erosive RA patients. Intra-articular delivery of miR-17 lipoplex was performed in collagen induced arthritis model in mice. Clinical, histological and structural effects were studied over the course of arthritis. In depth studies of miR-17 mechanisms of action were performed in primary RA-FLS isolated from RA synovial tissue. Results: Among others, miR-17-5p expression was reduced in erosive RA. miR-17 transfection in arthritic paws significantly reduced clinical inflammation. Moreover, synovial B cells, T cells, macrophages and polynuclear neutrophils infiltrates were significantly reduced. Structural damage was also decreased as shown by a reduction in the number of osteoclasts and erosion score by CT analysis. Pro-inflammatory cytokines of the IL-6 family, STAT3 target genes and IL-1β expression were also significantly reduced, but not TNF-alpha. miR17 directly targeted the 3'-untranslated region of STAT3 and JAK1. STAT3 and JAK1 mRNA and protein expression were reduced in RA-FLS following miR-17 transfection. STAT3 and JAK1 mRNA and activation of STAT3 as assessed by immunohistochemistry were also reduced in injected paws. Conclusion: We demonstrate an anti-inflammatory and anti-erosive role of miR-17 in vivo. This effect involves the suppression of the IL-6 family autocrine amplifying loop through the direct targeting of JAK1 and STAT3 as shown in RA-FLS. Disclosure of Interests: None declared